Short-term variations of mycosporine-like amino acids in the carrageenan-producing red macroalga Mazzaella laminarioides (Gigartinales, Rhodophyta) are related to nitrate availability - Navarro Martinez, Nelso Patricio; Korbee, N.; Jofre, J.; Figueroa, F. L. (My University, 2021)
The effect of solar UV radiation exposure and NO3- supply on mycosporine-like amino acids (MAAs) accumulation in the carrageenan-producing red macroalga Mazzaella laminarioides in a short-term period was studied. Apical segments of M. laminarioides tetrasporophytes were exposed to three treatments of solar radiation (PAR [P], PAR+UV-A [PA], and PAR+UV-A+UV-B [PAB]) under 0.38 mM NO3- or without NO3- supply. Samples were taken at the following local times: 8:00 (initial value), 13:00, and 18:00, and at 8:00 on the following day. Short-term variations in total MAA content were observed, being this variation accounted by the interaction of radiation, time exposure, and NO3- treatments. The highest MAAs content (above 3 mg g(-1) DW) was observed at 13:00 under PA (without NO3-) and PAB (with NO3-), and at 18:00 under PA (with NO3-) and PAB (with NO3-) treatments. Four MAAs were identified: asterina-330, shinorine, palythine, and mycosporine-glycine. The content and percentage of each MAA varied during the experimental time. While the accumulation of shinorine and palythine varied according to NO3- supply, mycosporine-glycine did it according to the interaction of time exposure and radiation treatment. The short-term (hours) variations in total MAAs content and the concentration of each MAA as a response to the high solar irradiance received could be a prerequisite in intertidal species to thrive in a highly variable environment.
Keywords: rhodophyta; nitrate; photoprotection; solar irradiance; sub-antarctic; uv radiation; uv-absorbing compounds